A materialização do controle social na política de assistência social - Valle, Almadiva Gomes do (2018)
The main theme of this master's thesis is to analyze ter materialization of social control in the Social Assistance Policy in Porto Alegre. The function of social control is to regulate, supervise and deliberate the policy in the three spheres of government. As a theoretical basis, the categories of State, Civil Society and Social Policy were broadened giving support to this production. A bibliographical, documentary and empirical research was carried out. In the bibliographic research, the journals qualified as A1, A2, B1 and B2 by Capes were prioritized, having as a sample twelve articles that covered the research theme. The documentary research had as objective the rescue of the history of the Municipal Council of Social Assistance and the implantation of the Policy of Social Assistance, through the analysis of documents of the collection of the council. From the empirical research, nine subjects participated, being seven counselors and two board members. The study was anchored in the dialectical-critical method that went through the entire process of this dissertation. The reference for data analysis was content analysis, based on studies by Bardin (1977). The results obtained indicate that the Social Assistance Policy and the Council arise in a context of democratic expansion. Thus, popular participation became one of the pillars in the implementation and implementation of this policy and the council. It is noticed that, with the most radical resumption of neoliberalism in the country, there is a change of the political project in the administration of the municipality, occurring a significant decline in the advance of the policy. In the process of organizing the council, there was an articulation with the implementation of the policy, evidencing, therefore, its incidence in the construction of the same and the importance of this instance in the guaranteed of this process. Finally, there is a long way to achieve the participation of users in politics and the council of Porto Alegre, currently threatened by the processes of dismantling of rights.